(untitled) (Texas Journal of Engineering and Technology, 2023)
In the article is analyzed the technological process in the working chamber of the saw gin. Based on the data on the density and kinematics of the raw roller, the interaction of the saw and the raw roller is shown. The reasons for the formation of ginning defects in the fiber are shown